HUBUNGAN KETERAMPILAN MEMBACA PEMAHAMAN BERITA DENGAN KETERAMPILAN MENULIS BERITA - Nency, Afrilla Purya; Ermanto, Ermanto; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ The purpose of this study is to describe the skills of reading comprehension news eighth grade students of SMP Negeri 7 Padang, news writing skills class VIII SMP Negeri 7 Padang, and the relationship between the reading comprehension skills of news with news writing skills class VIII SMP Negeri 7 Padang. This research data is the result of the test scores of news writing skills using descriptive methods. Data were collected through performance tests. The results of this study are the skills of reading comprehension news eighth grade students of SMP Negeri 7 Padang are in good qualifying (81.58), news writing skills class VIII SMP Negeri 7 Padang are in good qualifying (80.14), and there is a relationship reading skills understanding of news with news writing skills class VIII SMP Negeri 7 Padang at significant level of 95%with degrees of freedom (n -1), which tvalue > ttable (12.57> 1.68). Ho refused and H1 accepted because the hypothesis testing results prove that tvalue bigger than ttable.Â Kata kunci: hubungan, membaca pemahaman, keterampilan, menulis berita